Error-correction processing in timing lights for measuring sprint performance: Does it work? - Altmann, S.; Ringhof, S.; Becker, B.; Woll, A.; Neumann, R. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To investigate if error-correction-processing (ECP) algorithms in timing lights are able to eliminate or reduce measurement errors (MEs) and false signals due to swinging arms or legs. Methods: First, a dummy was used to check if ECP generally works. Second, 15 male sport students performed sprints over 5 and 10 m. Timing lights with ECP and a high-speed camera as a gold standard were used to simultaneously capture the athletes when passing the timing lights at start, 5 m, and 10 m. MEs of the timing lights were calculated for hip and upper body. Results: The dummy condition revealed that ECP is able to eliminate MEs. In real sprint conditions, MEs were highest for timing light at start and when using the hip as a reference. Overall, out of 120 trials, only 4 false signals were not detected by ECP. They all occurred at the start timing light, with highest MEs being 0.263 s (hip) and 0.134 s (upper body). Regarding 5 and 10 m, all false signals were eliminated. Conclusions: As proven through video analyses, ECP eliminated almost all false signals. The largest MEs at the start timing light were associated with a distinct forward leaning of the athletes. Therefore, clear instructions concerning starting posture should be given to further improve measurement accuracy of the start timing light. This approach could also enhance comparisons between athletes. Nevertheless, based on the results, timing lights employing ECP can be recommended for measuring short sprints.